Peran Notaris dalam Transaksi Kredit dengan Menjaga Legalitas dan Keamanan Nasabah - Shafa Aprilia Abdul (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Credit agreement is a means of development to obtain credit, the credit recipient is bound by certain conditions and is an agreement made by the creditor and debtor based on the agreement or agreement of the creditor and debtor, while the creditor is obliged to provide money or credit to the debtor and the debtor is obliged to pay the principal and interest, and other costs according to the agreed time period between the two. The creditor is a person or legal entity that provides credit to the debtor. In practice, credit in large amounts is mostly issued by the Bank, because the Bank is a legal entity that can collect large funds from the community and distribute them back to the community in the form of credit. Credit is one of the banking activities provided to customers. However, in connection with the increasing occurrence of bad debts that make it increasingly difficult for banks to increase their activities and the existence of efforts not to carry out credit repayments made by customers, there needs to be a power for banks to be able to take legal action or execute property rights owned by customers who have committed default, therefore banks need to cooperate with officials who are able to guarantee the power of the execution action, one of which is a Notary. A Notary is a public official regulated by law arising from the needs of the community, who has the authority to make authentic deeds as regulated in Law Number 2 of 2014 concerning the Position of Notary. A notary is a profession of trust and is different from other professions where notaries in carrying out their positions are impartial.